La pedagogie interculturelle : entre multiculturalisme et universalisme - Pretceille, Martine A. (Linguarum Arena, 2018)
The author intends to show that intercultural education is characterized by two conflicting approaches - an exacerbation of differences, and a universalism that, unfortunately, tends to be confused with the ethical principle of universality. Indeed, the treatment of cultural heterogeneity implies lean analysis and action from a moral and pragmatic philosophical viewpoint, that understands the practices, discourses and behaviours as rooted not in culturally distinct, homogeneous and hermetic categories, but rather as part of a process of miscegenation and “creolization”. Learning to observe, listen, and be attentive to others is the way in which we experience otherness, while avoiding what one may call the “learning of a culture”. This experience has to be acquired and developed. Thus, taking into account culture does not mean the mere introduction of an additional variable, but mainly aims to build up a humanism of the otherness.